Professional Thinking and Socio-Psychological Features of Managers in Education - Irina V. Serafimovich; Natalia V. Shlyakhtina; Nadezhda I. Bobyleva (National Research Mordova State University, 2021)
Introduction. The strategic task of improving the quality of Russian education requires increasing the efficiency of education system management. The authors assume integration of cognitive and personal resources of the subject of activity. The researchers focus on professional thinking as one of the cognitive resources. The aim of the article is to study the relationship between professional thinking and the socio-psychological features of personality. Materials and Methods. The materials of the study were the data of a survey of 65 people. The authors used questionnaires and the method of analyzing problem situations. For statistical processing, the methods of mathematical statistics were used. Results. It is shown that the situational-suprasituational level of thinking is predominant. The relationship between the level of professional thinking and the flexibility of choosing strategies of behavior in conflict and stress is established. There are similarities between the talent pool and managers with experience in conflict and stress behavioral strategies, and differences in management motivations. The new socio-economic reality and changes in the educational environment suggest that the manager should be ready to solve new heterogeneous professional tasks, which require expanding the range of competencies and a different level of reality understanding, integrating their own psychological structures, where professional thinking will play a system-forming role. Discussion and Conclusion. The obtained results can be used in solving tasks of the Nation-wide Project "Educationˮ aimed at further training of teaching staff, and in administering the said programs of continuing education.